Alzheimer's Disease with Epileptiform EEG Activity: Abnormal Cortical Sources of Resting State Delta Rhythms in Patients with Amnesic Mild Cognitive Impairment. - Babiloni, Claudio; Noce, Giuseppe; Di Bonaventura, Carlo; Lizio, Roberta; Eldellaa, Ali; Tucci, Federico; Salamone, Enrico M; Ferri, Raffaele; Soricelli, Andrea; Nobili, Flavio; Famá, Francesco; Arnaldi, Dario; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Patients with amnesic mild cognitive impairment due to Alzheimer's disease (ADMCI) typically show a "slowing" of cortical resting-state eyes-closed electroencephalographic (rsEEG) rhythms. Some of them also show subclinical, non-convulsive, and epileptiform EEG activity (EEA) with an unclear relationship with that "slowing." OBJECTIVE: Here we tested the hypothesis that the "slowing" of rsEEG rhythms is related to EEA in ADMCI patients. METHODS: Clinical and instrumental datasets in 62 ADMCI patients and 38 normal elderly (Nold) subjects were available in a national archive. No participant had received a clinical diagnosis of epilepsy. The eLORETA freeware estimated rsEEG cortical sources. The area under the receiver operating characteristic curve (AUROCC) indexed the accuracy of eLORETA solutions in the classification between ADMCI-EEA and ADMCI-noEEA individuals. RESULTS: EEA was observed in 15% (N = 8) of the ADMCI patients. The ADMCI-EEA group showed: 1) more abnormal Aβ 42 levels in the cerebrospinal fluid as compared to the ADMCI-noEEA group and 2) higher temporal and occipital delta ( CONCLUSION: It can be speculated that in ADMCI-EEA patients, AD-related amyloid neuropathology may be related to an over-excitation in neurophysiological low-frequency (delta) oscillatory mechanisms underpinning cortical arousal and quiet vigilance.

Circulating miR-127-3p as a Potential Biomarker for Differential Diagnosis in Frontotemporal Dementia. - Piscopo, Paola; Grasso, Margherita; Puopolo, Maria; D'Acunto, Emanuela; Talarico, Giuseppina; Crestini, Alessio; Gasparini, Marina; Campopiano, Rosa; Gambardella, Stefano; Castellano, Anna Elisa; Bruno, Giuseppe; Denti, Michela A; et al. (J Alzheimers Dis, 2018)
Given the heterogeneous nature of frontotemporal dementia (FTD), sensitive biomarkers are greatly needed for the accurate diagnosis of this neurodegenerative disorder. Circulating miRNAs have been reported as promising biomarkers for neurodegenerative disorders and processes affecting the central nervous system, especially in aging. The objective of the study was to evaluate if some circulating miRNAs linked with apoptosis (miR-29b-3p, miR-34a-5p, miR-16-5p, miR-17-5p, miR-107, miR-19b-3p, let-7b-5p, miR-26b-5p, and 127-3p) were able to distinguish between FTD patients and healthy controls. For this study, we enrolled 127 subjects, including 54 patients with FTD, 20 patients with Alzheimer's disease (AD), and 53 healthy controls. The qRT-PCR analysis showed a downregulation of miR-127-3p in FTD compared to controls, while the levels of other miRNAs remained unchanged. Then, miR-127-3p expression was also analyzed in AD patients, finding a different expression between two patient groups. A receiver operating characteristic curve was then created for miR-127-3p to discriminate FTD versus AD (AUC: 0.8986), and versus healthy controls (AUC: 0.8057). In conclusion, miR-127-3p could help to diagnose FTD and to distinguish it from AD.

What Drives Country Differences in Cost of Alzheimer's Disease? An Explanation from Resource Use in the GERAS Study. - Reed, Catherine; Happich, Michael; Argimon, Josep Maria; Haro, Josep Maria; Wimo, Anders; Bruno, Giuseppe; Dodel, Richard; Jones, Roy W; Vellas, Bruno; Belger, Mark (J Alzheimers Dis, 2017)
BACKGROUND: Country differences in resource use and costs of Alzheimer's disease (AD) may be driven by differences in health care systems and resource availability. OBJECTIVE: To compare country resource utilization drivers of societal costs for AD dementia over 18 months. METHODS: GERAS is an observational study in France (n = 419), Germany (n = 550), and the UK (n = 526). Resource use of AD patients and caregivers contributing to >1% of total societal costs (year 2010) was assessed for country differences, adjusting for participant characteristics. RESULTS: Mean 18-month societal costs per patient were France €33,339, Germany €38,197, and UK €37,899 (£32,501). Caregiver time spent on basic and instrumental activities of daily living (ADL) contributed the most to societal costs (54% France, 64% Germany, 65% UK). Caregivers in France spent less time on ADL than UK caregivers and missed fewer work days than in other countries. Compared with other countries, patients in France used more community care services overall and were more likely to use home aid. Patients in Germany were least likely to use temporary accommodation or to be institutionalized at 18 months. UK caregivers spent the most time on instrumental ADL, UK patients used fewest outpatient resources, and UK patients/caregivers were most likely to receive financial support. CONCLUSION: Caregiver time on ADL contributed the most to societal costs and differed across countries, possibly due to use of community care services and institutionalization. Other resources had different patterns of use across countries, reflecting country-specific health and social care systems.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Caregivers; Cohort Studies; Cost of Illness; Europe; Female; Health Resources; Humans; International Cooperation; Male; Surveys and Questionnaires

PRNP P39L Variant is a Rare Cause of Frontotemporal Dementia in Italian Population. - Oldoni, Emanuela; Fumagalli, Giorgio G; Serpente, Maria; Fenoglio, Chiara; Scarioni, Marta; Arighi, Andrea; Bruno, Giuseppe; Talarico, Giuseppina; Confaloni, Annamaria; Piscopo, Paola; Nacmias, Benedetta; Sorbi, Sandro; et al. (J Alzheimers Dis, 2016)
The missense P39L variant in the prion protein gene (PRNP) has recently been associated with frontotemporal dementia (FTD). Here, we analyzed the presence of the P39L variant in 761 patients with FTD and 719 controls and found a single carrier among patients. The patient was a 67-year-old male, with a positive family history for dementia, who developed apathy, short term memory deficit, and postural instability at 66. Clinical and instrumental workup excluded prion disease. At MRI, bilateral frontal lobe atrophy was present. A diagnosis of FTD was made, with a mainly apathetic phenotype. The PRNP P39L mutation may be an extremely rare cause of FTD (0.13%).
Keywords: Aged; Atrophy; Frontal Lobe; Frontotemporal Dementia; Genetic Predisposition to Disease; Humans; Italy; Language; Magnetic Resonance Imaging; Male; Memory Disorders; Memory, Short-Term; Neuropsychological Tests; Prion Proteins; Prions; Temporal Lobe

Progression of Extrapyramidal Signs in Alzheimer's Disease: Clinical and Neuropathological Correlates. - Tosto, Giuseppe; Monsell, Sarah E; Hawes, Stephen E; Bruno, Giuseppe; Mayeux, Richard (J Alzheimers Dis, 2016)
BACKGROUND: Extrapyramidal signs (EPS) are frequent in Alzheimer's disease (AD) and core manifestation of related diseases, i.e., dementia with Lewy bodies and Parkinson's disease; furthermore, Lewy bodies and AD-type pathology occur in all three conditions. OBJECTIVE: To identify clusters of EPS progression over time and their clinical and neuropathological correlates. METHODS: 3,502 AD patients with longitudinal assessment from the National Alzheimer's Coordinating Center database were included; 394 provided neuropathological data. k-means algorithm was employed to identify clusters of EPS progression and those were compared in terms of cognitive profile, neuropsychiatric features and neuropathological findings. RESULTS: Three clusters of EPS progression were identified: no/low (n = 1,583), medium (n = 1,259), and high (n = 660) EPS burden. Compared to those with no/low and medium EPS, those with high EPS had greater cognitive and neuropsychiatric impairment, specifically hallucinations. Despite similar AD-pathology across the three clusters, the high EPS cluster had a significantly number of subjects diagnosed with dementia with Lewy bodies. CONCLUSIONS: Cluster analysis of EPS progression over time identified different subgroups of AD patients with distinct clinical and neuropathological features.
Keywords: Aged; Algorithms; Alzheimer Disease; Cluster Analysis; Databases, Factual; Disease Progression; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Severity of Illness Index